Thermoplastic polymer nanocomposites based on polydopamine-coated clay : preparation, structures and properties - Phua, Si Lei (2014)
Polymer/clay nanocomposites have been widely investigated over past three decades due to the dramatic boost in properties at low filler content. Although organoclay (clay modified with organic surfactants) is commonly used to reinforce the polymer, yet the reinforcing extent has yet reached the optimum performance. Besides, both organic surfactants (organic compounds with long hydrophobic tails and hydrophilic heads) and polymers are susceptible to photo-induced degradation especially in outdoor environments, making polymer/clay nanocomposites vulnerable in practical applications. In order to overcome the aforementioned problems, in this research, D-clay (polydopamine-coated clay) was studied as multifunctional filler to improve not only interfacial interactions with a wide range of polymer matrices but also stabilities of the nanocomposites. D-clay was incorporated into both elastomer (polyurethane) and semi-crystalline thermoplastic (polypropylene) systems. The structure-property relationships of the resultant nanocomposites were investigated using TEM, XRD, DMA, tensile testing, FTIR, TGA and DSC. In particular, the reinforcing mechanism of D-clay in polyurethane (PU) nanocomposites was studied with respect to surface chemistry, filler loading and filler size. On the other hand, the stabilizing function of D-clay was verified using polypropylene (PP) as the polymer matrix since PP is well-known for its poor UV stability.